The effect of co-creation on relationship quality: the role of outcome quality / Kurnia Endah Riana ... [et al.] - Riana, Kurnia Endah; Halim, Edy Rizal; Suroso, Suroso; Chairy, Chairy (Accounting Research Institute (ARI), 2022)
Co-creation has been proposed as a novel approach to building relationship marketing. Communication, interaction, and value creation which are the main elements of co-creation are the stages for building relational marketing. Although there is substantial research on the role of co-creation in relationship marketing, much of the work is conceptual. This study investigated the effect of the degree of co-creation on relationship marketing using the relationship quality construct, the mediating effect of satisfaction and trust, and the moderating role of outcome quality in this relationship. An experimental approach was employed to achieve those objectives. Study 1 tested the effect of the degree of co-creation on relationship quality and the mediation effect of satisfaction and trust in the relationship between the degree of co-creation and commitment. Study 2 extended the results by demonstrating the moderation role of outcome quality. The findings showed that the degree of co-creation affects relationship quality and confirm that satisfaction and trust mediate the influence of the degree of co-creation on commitment. The moderating effect of outcome quality was confirmed; when outcome quality is less than expected, the degree of co-creation affects relationship quality.